Discharge of groundwater flow to Potter Cove on King George Island, Antarctic Peninsula - U. Falk; A. Silva-Busso (Hydrology and Earth System Sciences, 2021)
There are only a small number of recent publications discussing glacial runoff in Antarctica, and even fewer of them deal with the groundwater flow discharge. This paper focuses on the groundwater flow aspects and is based on a detailed study performed on a small hydrological catchment, informally called Potter basin, located on King George Island (KGI; Isla 25 de Mayo), South Shetland Islands, at the northern tip of the Antarctic Peninsula. The basin is representative for the rugged coastline of the northern Antarctic Peninsula and is discussed as a case study for the possible future evolution of similar basins further to the south. A conceptual hydrogeological model has been defined using vertical electrical soundings (VESs), geological and hydrogeological surveying methods, geomorphological interpretation based on satellite imagery, permeability tests, piezometric level measurements, meteorological, geocryological and glaciological data sets. The transmissivities of the fluvial talik aquifer and suprapermafrost aquifer range from 162.0 to 2719.9×10-5 <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="69pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="40665a9f8679e57366a84e2eae168d57"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="hess-25-3227-2021-ie00001.svg" width="69pt" height="13pt" src="hess-25-3227-2021-ie00001.png"/></svg:svg> m 2 s −1 and in basaltic fissured aquifers from 3.47 to <mn ...